Utilizing Technology To Boost Brand Recognition In Sales of Thrift Stores - Tuti, Meylani; Wulandari, Adinda (Technium Social Sciences Journal, 2024)
The purpose of this study is to ascertain how Instagram and EWOM affect customer happiness and brand trust. Brand trust can be raised by introducing products on Instagram and featuring recommendations from customers who have made purchases. Thrifting is a company that is expanding right now, particularly among the young people in our study. A total of 209 thrift store shoppers made up the sample. The findings demonstrate that Instagram has a direct and indirect impact on brand trust and satisfaction. This isn't the case, though, with EWOM, which has no bearing on the brand through satisfaction. Social media can be utilized more by proprietors of thrift stores to promote their products and increase consumer confidence in the brands they carry.